Implementasi Metode Takrir dalam Menghafalkan Al Qu’ran bagi Santri di Ponpes Darul Fithrah Sukoharjo - Anwar, Chaerul; Ridho, Rosyid (ANWARUL, 2024)
This research was motivated by the many complaints from people memorizing the Qur'an. They find it difficult to memorize and carry it out. There is a method called the Takrir method for memorizing the Qur'an, as an effort to improve and maintain memorization so that it remains embedded in the heart. Based on the background above, the problem formulation can be taken, what is the process of implementing the Takrir method in memorizing the Al-Qur'an and what results are achieved in implementing this method in memorizing the Al-Qur'an and what is the evaluation practice. This research uses a qualitative descriptive method with a phenomenological approach. To collect data using interview, observation and documentation methods. In analyzing the data the author uses stages: reducing data, displaying data and drawing conclusions. The research results show: First, the process of implementing the Takrir method in memorizing the Qur'an at the Tahfidhz Darul Fithrah Tawangsari cottage is going well, this is based on the reality of implementing memorizing the Qur'an using the Takrir method. However, it is still not perfect, as can be seen from the several problems it faces. Second, the results that have been achieved from the Takrir method are good and successful, the indication is that Tahfidz students can memorize half a Juz of the Qur'an per month, this has met the target. As for the evaluation of the implementation of the Takrir method, deliberations will be carried out every 3 months according to the need to find out the ma'had targets that have been formulated.